Use of dexmedetomidine on parturient women and newborns after cesarean section. - F. A. Garagurbanli; G. T. Mamed-zade; E. M. Nasibova (Pediatric Anesthesia and Critical Care Journal, 2024)
Introduction Special requirements are imposed on anesthetic care in obstetrics, especially in preeclampsia: it is necessary to ensure protection of the mother's body from surgical trauma and, at the same time, to prevent negative impact on the fetus, to maximally preserve its adaptive regula- tory mechanisms responsible for postnatal adaptation. Preeclampsia is one of the most common complications of pregnancy, which leads to significant disruptions in the main life support systems of mothers in labor, up to and including death. Purpose of the study: To study the ef- fect of intravenous dexmedetomidine during cesarean section under spinal anesthesia in women with preeclampsia on the vital functions of the mother and newborns in the early neonatal period. Material and Methods The study was conducted at the Scientific Research Insti- tute of Obstetrics and Gynecology in Baku. A prospec- tive, double-blind, randomized, controlled clinical study of 110 parturient women with preeclampsia was con- ducted. Results and discussion After a 10-minute intravenous loading dose of dexme- detomidine in patients of group II, the degree of sedation was 2.2±0.24 points. At the height of anesthesia before skin incision, RASS in group I increased by 10.9% to moderate, and in group II it decreased accordingly by 8.6% (P>0.05) to mild. After fetal extraction, RASS in group I increased by 15.2% (P<0.05) by the end of the operation and 8 hours after its completion decreased by 9.8 (P>0.05) and 78.8% (P<0.05), respectively, relative to the initial stage. In the second group, the degree of se- dation at all stages of the study according to RASS re- mained stable within the range of -2.2 and -1.9 points (P>0.05)